Functional literacy, educational attainment and earnings - evidence from the international adult literacy survey - Kevin Denny; Colm Harmon; Sandra Redmond (Institute for Fiscal Studies (IFS), 2000)
In this paper a rich and innovative dataset, the International Adult Literacy Survey, is used to examine the impact of functional literacy on earnings. The IALS surveys 12 OECD countries and sub-regions via a consistent questionnaire and includes a number of tests of numeracy and literacy, as well as basic labour market information. This paper examines the effect of these skills on labour market earnings for the Republic of Ireland, Northern Ireland, and for Great Britain. The estimates suggest that while ability has a role in determining earnings the dominant factor remains formal education. It is shown that, particularly for Great Britain, there is a positive interaction between the test score and education in determining earnings.
Keywords: 330; Analphabetismus; Bildungsertrag; OECD-Staaten